Development of Google Sites–Based Interactive Learning Multimedia Integrating Problem-Based Learning (PBL) for Acid–Base Concept - Ramli, Munasprianto; Badhri Alli Syahputra (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This research develops interactive learning multimedia based on Google Sites with a Problem Based Learning (PBL) model to improve students' understanding of acids and bases. Using a 4D (Define, Design, Develop, Disseminate) model, this media contains videos, images, simulations, interactive quizzes, and virtual experiments. The instruments include interviews, needs questionnaires, validation sheets, and limited trials. The research subjects consisted of expert lecturers, grade XI students, and chemistry teachers. The analysis was carried out descriptively, qualitatively, and quantitatively. The validation results showed that the media was very valid (material 90.79%, media 93.75%), with positive responses from students (90.1%) and teachers (97.6%). Thus, this medium is declared valid, practical, and effective for learning the chemistry of acid-base materials. This media is also designed to be easily accessible and used independently by students. Student involvement in problem-based activities is expected to improve critical thinking skills. The potential use of this medium is also open to other chemistry topics with relevant content adjustments.